Posttraumatic stress disorder symptom severity is associated with reduced Montreal Cognitive Assessment scores in a sample of Vietnam War Veterans. Issue 4 (26th March 2022) - Prieto, Sarah; Moody, Jena N.; Valerio, Kate E.; Hayes, Jasmeet P.
Abstract: The goal of the present study was to examine associations between posttraumatic stress disorder (PTSD) symptom severity, the number of stressors experienced, and cognitive outcomes in a sample of U.S. Vietnam War Veterans ( N = 274). Adults between 60 and 85 years of age completed a Vietnam Veterans Alzheimer's Disease Neuroimaging Initiative Project visit. A modified version of the Life Stressor Checklist‐Revised (LSC‐R) was used to assess the number of stressful experiences participants experienced, current PTSD severity scores were measured via the Clinician‐Administered PTSD Scale for DSM‐IV (CAPS‐IV), and cognition was assessed using the Montreal Cognitive Assessment (MoCA). Linear regressions were conducted to examine the effect of CAPS‐IV and LSC‐R scores on cognitive performance. Higher CAPS‐IV scores were associated with worse cognitive outcomes on the MoCA, Δ F (1, 264) = 12.686, p < .001, R 2 = .142. In contrast, the number of reported stressful experiences was not associated with cognitive outcomes. After accounting for multiple comparisons, findings indicated that CAPS‐IV severity scores were significantly associated with the MoCA memory index. In a sample of older Veterans, PTSD symptom severity, but not the number of reported stressors, was associated with poorer performance on a well‐established cognitive function screening tool. Analyses of specific MoCA domains indicated that memory may be driving this association. These findings suggest that highly arousing stressors characteristic of PTSD, rather than stressful experiences more broadly, contribute to this association. Future work can use these findings to explore whether treating PTSD symptoms may help maintain cognitive function during the aging process.